Antecedent of Revisit Intention for Halal Destinations - Handayani, Susi; Bismala, Lila; Hasibuan, Lailan Safina; Nor, Mhd Roslan Mhd; Prasetyo, Yoyok (Global Review of Islamic Economics and Business, 2025)
The importance of religiosity in halal tourism is the reason for this study. Religiosity is expected to influence and strengthen tourists' intention to return to halal destinations. The purpose of this study is to analyze the moderating role of religiosity in the influence of Electronic-Word of Mouth and Theory of Planned Behavior on revisit intention. Using the Purposive Sampling method, researchers obtained valid data from 201 respondents. The collected quantitative data was processed with the help of SmartPLS, to test the direct and moderation relationships between the research variables. The results of the study show that E-WOM influences revisit intention, and religiosity influences revisit intention. The results of this study can be utilized by halal destination managers, so that they can monitor reviews in E-WOM that influence revisit intention